Assessment of Noise Related Disorders among Health Care Personnel: A Cross-Sectional Study in Shiraz Hospitals - masoud neghab; ahmad soltanzadeh; roghayeh abedini; jafar hasanzadeh; saeed sarvestani (Shiraz University of Medical Sciences, 2014)
Background: Noise pollution has a particular importance in quiet environments such as hospitals. The main objective of this study was to evaluate the effects of noise exposure on the auditory system, blood pressure and precision, concentration and other psycho-neural components.Methods: This cross-sectional study was carried out in three large hospitals of Shiraz, during the period of 2012 to 2013. The study population consisted of 81 health care personnel (the exposed group) and 79 non-exposed individuals (the referent group). Day and night time sound levels were measured at different wards of the hospitals by a sound level meter (B&K 7110). Hearing status was assessed by pure tone audiometry of subjects by an Interacoustic AD27 audiometer. Blood pressure was measured with a mercury sphygmomanometer at resting time and psycho-neural components including sleep disturbances, headache, irritability and ... were evaluated by a questionnaire devised and validated for this purpose. Data were analyzed by SPSS 16 software.Results: Average sound pressure level for the exposed group (65.32±5.23 dB) was significantly higher than that of the referent group (53.26±2.46 dB) (P<0.05). Similarly, the mean values of permanent threshold shift (dB) as well as systolic and diastolic blood pressure were significantly higher in the exposed group than in their counterpart individuals (P<0.05). Likewise, symptoms such as headache and irritability were significantly more common among the exposed subjects. Conclusion: The findings suggest that exposure to sub-TLV levels of noise (recommended by ACGIH) in hospital environments is also associated with decreased hearing threshold, increased blood pressure, and prevalence of psycho-neural disorders.